The Josephin domain (JD) containing proteins are predicted to bind to the same interactors: Implications for spinocerebellar ataxia type 3 (SCA3) studies using Drosophila melanogaster mutants - Sousa e Silva, Rita; Sousa, André Dias; Vieira, Jorge; Vieira, Cristina P. (Frontiers in Molecular Neuroscience, 2023)
Spinocerebellar ataxia type 3, also known as Machado-Joseph disease (SCA3/ MJD), is the most frequent polyglutamine (polyQ) neurodegenerative disorder. It is caused by a pathogenic expansion of the polyQ tract, located at the C-terminal region of the protein encoded by the ATXN3 gene. This gene codes for a deubiquitinating enzyme (DUB) that belongs to a gene family, that in humans is composed by three more genes (ATXN3L, JOSD1, and JOSD2), that define two gene lineages (the ATXN3 and the Josephins). These proteins have in common the N-terminal catalytic domain (Josephin domain, JD), that in Josephins is the only domain present. In ATXN3 knock-out mouse and nematode models, the SCA3 neurodegeneration phenotype is not, however, reproduced, suggesting that in the genome of these species there are other genes that are able to compensate for the lack of ATXN3. Moreover, in mutant Drosophila melanogaster, where the only JD protein is coded by a Josephin-like gene, expression of the expanded human ATXN3 gene reproduces multiple aspects of the SCA3 phenotype, in contrast with the results of the expression of the wild type human form. In order to explain these findings, phylogenetic, as well as, protein–protein docking inferences are here performed. Here we show multiple losses of JD containing genes across the animal kingdom, suggesting partial functional redundancy of these genes. Accordingly, we predict that the JD is essential for binding with ataxin-3 and proteins of the Josephin lineages, and that D. melanogaster mutants are a good model of SCA3 despite the absence of a gene from the ATXN3 lineage. The molecular recognition regions of the ataxin-3 binding and those predicted for the Josephins are, however, different. We also report different binding regions between the two ataxin-3 forms (wild-type (wt) and expanded (exp)). The interactors that show an increase in the interaction strength with exp ataxin-3, are enriched in extrinsic components of mitochondrial outer membrane and endoplasmatic reticulum membrane. On the other hand, the group of interactors that show a decrease in the interaction strength with exp ataxin-3 is significantly enriched in extrinsic component of cytoplasm.